Implementasi Kebijakan Subsidi Pupuk Di Desa Mulung Kecamatan Driyorejo Kabupaten Gresik - Umi Atyah Safinatun Najah; Lunariana Lubis (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2026)
This study aims to analyze the implementation of the subsidized fertilizer policy in Mulung Village, Driyorejo Subdistrict, Gresik Regency, using the policy implementation theory framework proposed by Van Meter and Van Horn. The subsidized fertilizer policy is a crucial instrument in agricultural sector development, designed to ensure the availability of affordable fertilizer for farmers, thereby enhancing agricultural productivity, improving farmers’ welfare, and supporting national food security. This study employs a qualitative approach with a case study design. Data collection was conducted through in-depth interviews, field observations, and document analysis involving various actors involved in the implementation of the subsidized fertilizer policy, such as agricultural extension workers, farmer groups, fertilizer shop owners, and beneficiary farmers. Data analysis was performed using an interactive analysis model through the stages of data reduction, data presentation, and conclusion. The research findings indicate that the implementation of the subsidized fertilizer policy in Mulung Village has generally proceeded through the mechanism of farmer registration using the e-RDKK system, the determination of fertilizer allocations based on the needs of farmer groups, and the distribution of fertilizer through official retail outlets. The presence of agricultural extension workers and farmer groups has been a key factor supporting the implementation of the policy at the village level. However, the implementation of this policy has not yet been fully optimal due to several constraints, such as limited allocations of subsidized fertilizer, the practice of selling fertilizer above the Maximum Retail Price (MRP), and distribution challenges at the local level. Research findings indicate that the success of policy implementation is influenced by resource factors, inter-organizational communication, the socioeconomic conditions of the community, and the attitudes of policy implementers. Therefore, strengthening oversight of fertilizer distribution, improving the farmer data collection system, and enhancing inter-agency coordination are crucial steps to enhance the effectiveness of subsidized fertilizer policy implementation.